O corpo em trânsito em meio às práticas comunicativas: processos de criação de Roberto Alencar - Dias, Wagner Miranda (2017)
This research investigates the paths of the artist's artistic composition - theater, dance and performance - Roberto Alencar, reflecting on his creative, authoring and communication processes, observing the procedures that involve his thought and practice in the production of his scene, highlighting the relations between drawing, verb and body. The investigation of the transit between languages inserted in the creative processes is essential to think critically about contemporary communication systems and networks, throwing glances on the construction of the diverse communicative objects that act in hybridization, revealing different modes of action and creative structures. The hypothesis is that the artist of the body who possesses consciousness and mastery of the visual / verbal transit of the scene arts, engendered as body space experience, can trigger effective creative and communicational processes between the stages of elaboration of the scene, with the artistic collective and with the public. The theoretical foundation is structured from the studies of Cecilia Almeida Salles, who investigate creation processes within the complexity of the systems; the authors RoseLee Goldberg, Silvia Fernandes and Flávio Desgranges, will be used in regard to historical and social reflection on the artist of the body. Renato Cohen will be convened to discuss performance and language issues; Christine Greiner, Helena Katz, Lucia Santaella, Norval Baitello, for concepts about image and body; Vincente Colapietro for his studies on Peircian semiotics and subjectivity. The theoretical framework proposes dialogues with thinkers fundamental to the study of body and culture (Edgar Morin, Zigmunt Bauman, Mikhail Bakhtin). The scientific methodologies will be the one of bibliographical research, seeking to establish a critical approach on the relation creation, authorship and communication and the field research, that will be based on the investigation of drawings, drafts, videos, audio recordings, interviews and documents of process